Karakterisasi Roti Manis Subtitusi Tepung Rumput Laut (Eucheuma Cotonii), dan Tepung Ubi Talas (Colocasia Esculenta L Schott) - Sri Oktaviani Pasi; Rahim Husain; Sutianto Pratama Suherman (Transbahasa, 2024)
This study aims to analyze the organoleptic and chemical characteristics of sweet bread substituted with seaweed flour (Eucheuma cottonii) and taro flour (Colocasia esculenta L. Schott). The research used four treatments with different ratios of seaweed flour to taro flour, namely P1 (0%:100%), P2 (30%:70%), P3 (35%:65%), and P4 (40%:60%), each with two replications. The parameters tested included fat content, protein content, moisture content, ash content, and organoleptic tests using the hedonic method. The study was designed using a Completely Randomized Design (CRD). Chemical data were analyzed using ANOVA and further tested with Duncan's test, while organoleptic data were analyzed using the Kruskal-Wallis test. The results showed that the P4 treatment (40% seaweed flour: 60% taro flour) provided the best results in organoleptic tests. The Kruskal-Wallis test results indicated that the different proportions of seaweed flour and taro flour significantly affected the appearance, aroma, color, texture, and taste of the resulting sweet bread. The chemical characteristics of the sweet bread in the best treatment (P4) were 2.58% fat content, 8.69% protein content, 27.07% moisture content, and 1.75% ash content. This research indicates that the substitution of seaweed flour and taro flour can produce sweet bread with good sensory quality and a chemical composition that is potential for food product diversification.